Properties of nanostructured Ni-doped Sn2S3 thin films – doping concentration effect. (28th July 2016) - Gnanamuthu, S. Joshua; Punithavathy, I. Kartharinal; Jeyakumar, S. Johnson; Usharani, K.; Balu, A.R.
Abstract: Nanostructured Ni-doped Sn2 S3 thin films with Ni concentrations (0, 1, 2 and 3 wt.%) were prepared on glass substrates by spray pyrolysis technique at 400 °C. From the structural studies, it is observed that both the undoped and doped films exhibit orthorhombic crystal structure with (2 1 1) preferential orientation. Crystallite size increased from 22.94 to 27.80 nm with Ni doping. SEM images confirmed the presence of nanoneedles in the doped films. Film transparency increased with doping and optical band gap is found to be blue shifted which is related to Burstein–Moss (BM) effect. All the films have resistivity in the order of 10 −1 Ω-cm, which decreased with Ni doping. From the structural, morphological, optical and electrical properties, it is observed that the Sn2 S3 film coated with 2 wt.% Ni doping had better physical properties.